Kolaborasi Antar Generasi Muda - Lansia Untuk Optimalisasi dalam Penerapan Teknologi Vertical Green Entrepreneurship - Rosa, Tina; Nurhastuti, Tiwi; Marliana, Thika; Nuraini, Ani; Siswani, Sri; Nurminngsih, Nurminngsih; Agustin, Dinni; Sholihah, Siti M; Ahamadun, Ahamadun; Asim, Asim; Rohmawan, Kwarnanto; Nurdian, Budi; M Kurnianto, Wahyu; Setiawan, Dharma; Juliantika, Silvi Sumanti (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2026)
Background: Global challenges such as climate change, food crises, and massive urbanization demand innovative solutions. Vertical Green Entrepreneurship (VGE), which combines vertical farming technologies (hydroponics, aeroponics, aquaponics) with green entrepreneurship principles, offers a sustainable answer by utilizing limited urban space to produce fresh agricultural products, reduce carbon footprints, and create economic opportunities. Objective: This activity aims to develop a collaborative thinking framework across generations and disciplines in implementing VGE, including the development of agricultural product systems, integrated mobile-based monitoring technology, and a dual marketing system (agro-tourism visits and direct sales). Methods: The activity was conducted directly at the VGE site, Ladang Farm Technology. The approach employed collaboration between the younger generation (university students) and the elderly (lecturers entering retirement), enabling the implementation of an integrated technology system from upstream (agriculture) to downstream (marketing). Results: The VGE concept emerges as an innovative and sustainable solution. However, optimizing its application requires a holistic and collaborative approach. The unique synergy between the younger generation (Gen Z & Millennials) and the elderly generation (Baby Boomers & Gen X) is key to success. This cross-generational collaboration is not only strategic but also essential for creating sustainable impact. Conclusion: Cross-generational and cross-disciplinary collaboration is key to optimizing VGE. A holistic approach from production to technology-based marketing enhances the effectiveness of green entrepreneurship and creates sustainable economic and environmental impacts